2022
DOI: 10.2196/36673
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID Optimal Health Program (LC-OHP) to Enhance Psychological and Physical Health: Protocol for a Feasibility Randomized Controlled Trial

Abstract: Background Long COVID is a collection of symptoms that develop during or following a confirmed or suspected case of COVID-19, which continue for more than 12 weeks. Despite the negative impact of long COVID on people’s lives and functioning, there is no validated treatment or even rehabilitation guidance. What has been recommended thus far is the adoption of holistic management approaches. The Optimal Health Program (OHP) is a brief 5-session, plus booster, psychosocial program designed to support … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“… 40 , 44 , 45 However, as LC does not fit into a specific diagnostic category, the Long COVID–Optimal Health Programme (LC–OHP) was adapted from the existing OHP and tested within a feasibility randomised controlled trial (RCT). 46 , 47 This study aimed to explore the feasibility and acceptability of delivering the LC–OHP to people with LC, and their perceptions and experiences with using it. The objectives were as follows: to identify views on the LC–OHP; to explore the potential for the programme to support mental and physical wellbeing; and to gain suggestions for improving the programme.…”
Section: Introductionmentioning
confidence: 99%
“… 40 , 44 , 45 However, as LC does not fit into a specific diagnostic category, the Long COVID–Optimal Health Programme (LC–OHP) was adapted from the existing OHP and tested within a feasibility randomised controlled trial (RCT). 46 , 47 This study aimed to explore the feasibility and acceptability of delivering the LC–OHP to people with LC, and their perceptions and experiences with using it. The objectives were as follows: to identify views on the LC–OHP; to explore the potential for the programme to support mental and physical wellbeing; and to gain suggestions for improving the programme.…”
Section: Introductionmentioning
confidence: 99%
“…The study protocol and outcomes from the randomised controlled trial (RCT) are reported separately. 34,38,39…”
Section: Governance and Ethical Approvalsmentioning
confidence: 99%
“…This study is part of a wider randomised clinical trial that assessed the feasibility of the Long COVID Optimal Health Programme (LC‐OHP), a psychosocial educational support programme for mental and physical wellbeing customised for people with LC 34,35 . Participants in this study were those randomised to the intervention group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations